A formação integral dos sujeitos do Novo Ensino Médio: desafios e alternativas no processo da implementação da política pública na Rede Jesuíta de Educação - Melo, Fernando Almeida de (Universidade do Vale do Rio dos Sinos, 2024)
The research analyzes how the educational principles assumed by the High School reform were incorporated by two schools of the Jesuit Education Network (RJE), as elements capable of reinforcing the perspective of comprehensive student education and as a condition for addressing the complex agenda of contemporary world priorities, interfacing with the RJE's educational proposal. It problematizes how the curriculum reform has been conducted by the managers of the surveyed schools, considering the context in which the State reconsiders its role, dispensing with its condition as a regulator and evaluator of national educational policy. The main objective of the research is to analyze how RJE schools incorporated the educational principles presented by the High School reform. The process of appropriating the guidelines linked to the reform is analyzed based on the conceptions of youth, contemporary society, and the world of work adopted by the surveyed schools. Methodologically, this research is configured as a case study. Data collection was conducted through document analysis and semi-structured interviews with managers involved in implementing the new High School. It was possible to verify that the surveyed schools incorporated into their curricula principles that reinforced the conception of comprehensive student education advocated by the RJE. It is concluded that this fact reveals an opportunity to update the guiding documents of the units' pedagogical projects, allowing the RJE to revisit its guidelines considering the researched concepts. The intervention is based on creating an evaluation system that includes cognitive, socio-emotional, and spiritual-religious dimensions, to demonstrate how the High School curriculum reinforces its perspective of comprehensive education and with systematic monitoring of the students.
Keywords: Ensino Médio; Reforma curricular; Juventudes; Mundo do trabalho; High school; Curriculum reform; Youth; World of work; ACCNPQ::Ciências Humanas::Educação